DESCRIPTION THE LEVEL OF SATISFACTION OF HOSPITALIZED PATIENTS FOR SERVING FOOD AT WANGAYA HOSPITAL DENPASAR - NI MADE DEWI PURNAMASARI; Ida Ayu Eka Padmiari; Ni Made Yuni Gumala (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
Satisfaction is one aspect of assessing the quality of health services including the presentation of food in hospitals. The purpose of this study was to describe the level of patient satisfaction at the presentation of regular form food at Wangaya Hospital Denpasar. The type of research used was observational with a cross-sectional study design, and samples were taken by purposive sampling with inclusion criteria: male and female hospitalized patients aged ≥18 years who were treated to Wangaya Denpasar Hospital, patients received regular form of food, not illiterate and able to communicate, has signed the PSP form and is disposed as a research sample. As for the exclusion criteria are patients who get a low salt diet. Based on the calculation the number of samples was set at 47 people. The results of the level of satisfaction of patients in Wangaya Hospital were 107%, which meant that patients were satisfied with the presentation of food, because it was above the standard level of satisfaction (≥90%). Based on the Cartesian diagram analysis, there are 4 aspects that are the top priority so it needs to be improved, 9 aspects must be maintained, 10 aspects with low priority and 2 aspects are considered excessive.